2005
DOI: 10.1590/s0103-50532005000200014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the induction period of the Belousov-Zhabotinsky reaction

Abstract: No presente estudo apresentamos a dependência do tempo de indução da reação BelousovZhabotinsky (BZ) em função da concentração inicial do ácido malonico, bromato e cerium. Os resultados mostram que o tempo de indução aumenta com o aumento da concentração de bromato e tal comportamento não coincide com o mecanismo proposto para as reações BZ. Propomos então que uma competição cinética entre a bromação do ácido malonico e a oxidação dos ácidos bromomalonico e malonico seja o caminho para entender este mecanismo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
(8 reference statements)
2
17
0
Order By: Relevance
“…The reaction was carried out at 25.8 °C and the data recording lasted for 12 850 s. Figure depicts the dynamic variation of the absorbance values for cerium (IV) ions as a representative of [Ce 4+ ]. As can be seen in Figure , an induction period of about 830 s precedes the concentration oscillations in our experiment, which is in agreement with the findings reported by Cadena et al…”
Section: Methodssupporting
confidence: 94%
“…The reaction was carried out at 25.8 °C and the data recording lasted for 12 850 s. Figure depicts the dynamic variation of the absorbance values for cerium (IV) ions as a representative of [Ce 4+ ]. As can be seen in Figure , an induction period of about 830 s precedes the concentration oscillations in our experiment, which is in agreement with the findings reported by Cadena et al…”
Section: Methodssupporting
confidence: 94%
“…According to the GTF model [4] the length of IP is determined by the concentration of bromomalonic acid (BrMA). The crucial amount of BrMA necessary for the onset of oscillations is produced through two main pathways: (a) the bromination of the enol form of malonic acid by Br 2 and (b) the reaction between Br 2 and the malonyl radical formed in the Ce-MA subsystem [8]. Previous works showed a direct relationship between the enolization constant of different organic substrates in BZ-like oscillating systems and the length of the IP [911].…”
Section: Introductionmentioning
confidence: 99%
“…From figure , it was observed that the number of oscillations increased while as amplitude and induction period of the oscillations evolved a decreasing trend when perturbed before induction period. The change in the amplitude of the oscillations on perturbation testifies the interaction between Mac 3H and the metal catalyst i. e., cerium.…”
Section: Resultsmentioning
confidence: 96%